TRPV1 antagonists that cause hypothermia, instead of hyperthermia, in rodents: Compounds' pharmacological profiles, in vivo targets, thermoeffectors recruited and implications for drug development. (16th February 2018) - Garami, A.; Pakai, E.; McDonald, H. A.; Reilly, R. M.; Gomtsyan, A.; Corrigan, J. J.; Pinter, E.; Zhu, D. X. D.; Lehto, S. G.; Gavva, N. R.; Kym, P. R.; Romanovsky, A. A.
Abstract: Aim: Thermoregulatory side effects hinder the development of transient receptor potential vanilloid‐1 (TRPV1) antagonists as new painkillers. While many antagonists cause hyperthermia, a well‐studied effect, some cause hypothermia. The mechanisms of this hypothermia are unknown and were studied herein. Methods: Two hypothermia‐inducing TRPV1 antagonists, the newly synthesized A‐1165901 and the known AMG7905, were used in physiological experiments in rats and mice. Their pharmacological profiles against rat TRPV1 were studied in vitro. Results: Administered peripherally, A‐1165901 caused hypothermia in rats by either triggering tail‐skin vasodilation (at thermoneutrality) or inhibiting thermogenesis (in the cold). A‐1165901‐induced hypothermia did not occur in rats with desensitized (by an intraperitoneal dose of the TRPV1 agonist resiniferatoxin) sensory abdominal nerves. The hypothermic responses to A‐1165901 and AMG7905 (administered intragastrically or intraperitoneally) were absent in Trpv1 −/− mice, even though both compounds evoked pronounced hypothermia in Trpv1 +/+ mice. In vitro, both A‐1165901 and AMG7905 potently potentiated TRPV1 activation by protons, while potently blocking channel activation by capsaicin. Conclusion: TRPV1 antagonists cause hypothermia by an on‐target action: on TRPV1 channels on abdominal sensory nerves. These channels are tonically activated by protons and drive the reflectory inhibition of thermogenesis and tail‐skin vasoconstriction. Those TRPV1 antagonists that cause hypothermia further inhibit these cold defences, thus decreasing body temperature. Significance: TRPV1 antagonists (of capsaicin activation) are highly unusual in that they can cause both hyper‐ and hypothermia by modulating the same mechanism. For drug development, this means that both side effects can be dealt with simultaneously, by minimizing these compounds' interference with TRPV1 activation by protons.